Answer:
see the explanation
Step-by-step explanation:
we have
[tex]x^2+6x+y^2-16y=-9[/tex]
Convert the equation of the circle in center radius form
Group terms that contain the same variable
[tex](x^2+6x)+(y^2-16y)=-9[/tex]
Complete the square twice. Remember to balance the equation by adding the same constants to each side
[tex](x^2+6x+9)+(y^2-16y+64)=-9+9+64[/tex]
[tex](x^2+6x+9)+(y^2-16y+64)=64[/tex]
Rewrite as perfect squares
[tex](x+3)^2+(y-8)^2=8^2[/tex]
The center of the circle is (-3,8)
The radius of the circle is 8 units
Verify each statement
A. The center of the circle is (3,-8).
False
The center of the circle is (-3,8)
B. The circle is tangent to the x-axis
True
The circle is tangent to x=5 and x=-11 and is tangent to y=0 and y=16
Remember that y=0 is the x-axis
C. The circle has a radius of 64
False
The radius of the circle is 8 units